2013
DOI: 10.1002/glia.22463
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid induces astrocyte‐dependent neurite outgrowth from cultured rat primary cortical neuron via modulation of tPA/PAI‐1 activity

Abstract: Tissue plasminogen activator (tPA) is expressed in several regions of brain and plays regulatory roles such as neurite outgrowth, synaptic plasticity and long term potentiation. The activity of tPA is regulated by an endogenous inhibitor plasminogen activator inhibitor-1 (PAI-1), which is expressed mainly in astrocytes. Valproic acid (VPA), a histone deacetylase inhibitor that is used for the treatment of epilepsy and bipolar disorders, promotes neurite extension, neuronal growth and has neuroprotective effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 79 publications
1
18
0
Order By: Relevance
“…The VPA treatment in our current findings led to significantly reduced PAI-1 expression. This effect of VPA has been noted previously on in vitro expression of PAI-1, and recently in a human model by others in our group [ 19 , 28 ]. This may be clinically relevant since fibrinolytic status in man is determined by t-PA/PAI-1 ratios.…”
Section: Discussionsupporting
confidence: 83%
“…The VPA treatment in our current findings led to significantly reduced PAI-1 expression. This effect of VPA has been noted previously on in vitro expression of PAI-1, and recently in a human model by others in our group [ 19 , 28 ]. This may be clinically relevant since fibrinolytic status in man is determined by t-PA/PAI-1 ratios.…”
Section: Discussionsupporting
confidence: 83%
“…Increased expression of PAI-1 reduced tPA activity in LPS plus propofol-treated rat primary astrocytes. Consistent with the critical role of tPA activity in the regulation of neurite extension (Cho et al 2013), the diminished tPA activity in astrocyte culture supernatants resulted in decreased neurite extension when administered to cultured rat primary cortical neuron. The results from the present study suggest that propofol, especially in immunologicallychallenged situation, dysregulates tPA/PAI-1 system in brain.…”
mentioning
confidence: 56%
“…The neurite extension was induced by the addition of astrocytes culture supernatants, which showed dependence on the overall level of tPA activity (Cho et al 2013). As expected from the increased PAI-1 activity and reduced tPA activity, addition of astrocytes culture supernatant treated with LPS to rat Fig.…”
Section: Propofol and Lps Treated Astrocytes Conditioned Media Decreamentioning
confidence: 97%
“…PAI-1 is abundantly expressed in infarcted myocardium, but the pathogenic role of plasma PAI-1 plasma remains unknown in patients with Parkinson's disease (30). Cho et al (31) have previously demonstrated that valproic acid may induce astrocyte-dependent neurite outgrowth from cultured rat primary cortical neuron via modulation of tissue plasmogen activator PAI-1 activity. Previous studies have reported changes in the plasminogen activator system and the inhibitors PAI-1 and PAI-2 in posttraumatic lesions in the central nervous system and brain injuries (32,33).…”
Section: Discussionmentioning
confidence: 99%